2004
DOI: 10.1158/0008-5472.can-04-2097
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synaptojanin 2 in Glioma Cell Migration and Invasion

Abstract: The small GTPase Rac1 is thought to play an important role in cell migration and invasion. We have previously identified synaptojanin 2, a phosphoinositide phosphatase, as an effector of Rac1. Here, we show that small interfering RNA-mediated depletion of either Rac1 or synaptojanin 2 inhibits invasion of SNB19 and U87MG glioblastoma cells through Matrigel and rat brain slices. Depletion of Rac1 or synaptojanin 2 also inhibits migration of SNB19 and U87MG cells on glioma-derived extracellular matrix. In additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 40 publications
10
138
0
Order By: Relevance
“…High-grade gliomas exhibit aggressive behavior, which is manifested by rapid cellular migration under culture conditions in vitro (12,50). Using a standard "scratch" assay after the cells become confluent in culture dishes, we found that enhanced expression of miR-146a significantly reduced the rate of migration of Ink4a/Arf Ϫ/Ϫ Pten Ϫ/Ϫ Egfr vIII astrocytes compared to the same cells transduced with a control lentivirus (Fig.…”
Section: Egfr Activation and Pten Inactivation Synergistically Inducementioning
confidence: 85%
“…High-grade gliomas exhibit aggressive behavior, which is manifested by rapid cellular migration under culture conditions in vitro (12,50). Using a standard "scratch" assay after the cells become confluent in culture dishes, we found that enhanced expression of miR-146a significantly reduced the rate of migration of Ink4a/Arf Ϫ/Ϫ Pten Ϫ/Ϫ Egfr vIII astrocytes compared to the same cells transduced with a control lentivirus (Fig.…”
Section: Egfr Activation and Pten Inactivation Synergistically Inducementioning
confidence: 85%
“…Notably, our results contrast with those obtained in human glioma cells inhibiting Rac by small interfering RNA (siRNA)-mediated depletion. 28,29 One potential explanation for this discrepancy could be that compare to siRNA-mediated depletion of Rac1, the dominant negative Rac1 inhibits all isoforms of Rac (Rac1, Rac2 or Rac3) due to their high structural homology or other downstream signaling molecules. Therefore, it remains to be further studied the specific function of Rac1 in rat C6 glioma cells by siRNA-mediated depletion of Rac1, Rac2 or Rac3.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with lamellipodia by the inhibition of Rac1 reduces migration. This also causes GBM cells to acquire a relatively round shape without extending cell processes (Chuang et al, 2004). In contrast, collapse of actin stress fiber formation by the inhibition of RhoA promotes migration (Salhia et al, 2005).…”
Section: Migration/invasionmentioning
confidence: 99%